Revisiting the concept of waqf : its maintenance, issues and challenges - Hayatullah Laluddin,; Sayed Sikandar Shah Haneef,; Mohammad Tahir Sabit Haji Mohammad,; Maya Puspa Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Philanthropic endowment or wqaf represents a form of long lasting charity with potential profits or benefits meant for the spiritual and economical improvement of the society. This study attempts to revisit the concept of waqf by analysing its literal and technical meanings, its legitimacy in the light of the Qur’an and Sunnah. It also analysis some classical and contemporary views pertaining its conceptualization and traces its origin in the Islamic heritage. Istibdal, exchange of the waqf property, as a means of viability of waqf property and its relevant challenges are also dealt with. This paper is based on library research and use qualitative method. Having analysed, the relevant data the authors arrived at the conclusion that future efforts need to be made to develop the concept of waqf based on maqasid shari’ah while in tandem need to develop a universal and comprehensive vision of shari’ah based on its objectives. Both concepts must be revisited, reviewed, and revised to restore the dynamism of the concept of waqf hence, making it an effective tool for alleviation of the poverty and the distribution of wealth among the different sections of the society in equitable manner.